The Role of Social Media Instagram @Partaibulanbintang.Official in Building Communication for the 2024 Political Year - Gustam, Ratry Aisyah; Ramadhan, Panji Bhaskara (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
The world of communication today is increasingly very broad both in terms of reach and effect. Especially with the presence of various media options to be able to accommodate the message you want to spread. One of these media choices is social media. And how social media can be the main tool for disseminating information and messages from political parties to the public, especially their sympathizers. Social media especially Instagram then becomes the main choice of political parties today to be able to build interaction with party sympathizers. The Bulan Bintang Party (PBB), which in the 2019 general election was ranked 14th in total votes, made PBB have to work extra to be able to reach more sympathizers in the 2024 political year. This research was conducted in June 2023. One of the publication activities that is actively carried out is through the dissemination of information on all activities, messages and information from the party to be conveyed to the public through the social media medium Instagram @partaibulanbintang.official. The UN Party Imaging and Public Communication Team said that the official UN Instagram account has become a platform that is the entry point for interaction between the community and the UN through various questions via Direct Message.